IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR NEGERI KOTA SINGKAWANG - Risa Kusuma; Mashudi Mashudi; Tahmid Sabri (Universitas Tanjungpura, 2020)
AbstractThe problem in this study is how planning, implementation and assessment in implementing a scientific approach through integrated thematic learning that aims to make students more interested in finding and building their own meaningful and enjoyable knowledge through the implementation of scientific approaches at Singkawang 1 Public Elementary School and 23 Public Elementary Schools Singkawang. This research was conducted in Singkawang 1 Public Elementary School and Singkawang 23 Public Elementary School. This research is a qualitative descriptive study. The subjects of this study were classroom teachers and fourth grade students at Singkawang 1 Public Elementary School and Singkawang Elementary School 23. Data collection techniques used are observation, interviews, and documentation. Data collection tools are interview sheets, observation sheets, and documentation. Data analysis using steps: data reduction, data display, and conclusion drawing. Techniques for checking the validity of data using triangulation. The results of the study show that grade IV teachers have carried out learning with a scientific approach in integrated thematic learning. The scientific approach implemented includes; observe, ask, try, reason, and communicate. With the scientific approach to integrated thematic learning, students become more active in learning, especially being confident and brave to ask questions, reason and express ideas or opinions, so that they gain knowledge based on direct experience. The assessment used is authentic assessment. Keywords: scientific approach, integrated thematic learning